(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate patient satisfaction with fasting and receiving 12.5% maltodextrin solution before elective surgery. Subjects and Methods: A prospective descriptive study was conducted on 154 patients who underwent preoperative fasting and received 12.5% maltodextrin before elective surgery at Post Office Hospital from July to August 2025. Results: The patients had a mean age of 48.8 ± 15.0 years, with most classified as ASA I – II (97.4%). The proportion fasting for more than 12 hours before surgery was 89.0%, and 79.9% consumed 12.5% maltodextrin more than 3 hours prior to surgery. Preoperatively, most patients did not feel thirsty (66.2%) or hungry (61.7%); nausea and vomiting were infrequent (11.7% and 2.6%, respectively). Overall satisfaction was 77.3%. Higher satisfaction rate due to reduction in hunger (91.6%), thirst (88.3%), nausea (90.0%) and vomiting (96.1%) criteria. Conclusion: Administration of 12.5% maltodextrin before elective surgery is safe, alleviates sensations of hunger, thirst, dry mouth, nausea, vomiting, and improves patient satisfaction.